Alexandra Scheiman, Il diario perduto di Frida Kahlo (Altre Modernità, 2018)
Alexandra Scheiman, Il diario perduto di Frida Kahlo(Milano, Rizzoli, 2018, 322 pp. ISBN 978- 88- 17- 10337-4)di Marta Rita Pellecchia